Changes in the Sophic Function of Female Characters in 20th-Century Literary Works - Szabó, Tünde (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The present study examines in what ways three 20th-century works, Yevgeny Zamyatin’s short story The Flood, Viktor Yerofeyev’s novel Russian Beauty and Ludmila Ulitskaya’s novel Sonechka, are connected to Fyodor Dostoyevsky’s novel Crime and Punishment. Beyond the surface parallels in the plot, the presence of a poetic-semantic complex rooted in mythological thinking is observable. The sophic function, which is transformed in each of the successive works, is one of the components of the said complex.